PENDEKATAN PENDIDIKAN AGAMA HINDU DALAM MENGATASI KRISIS MORAL DI KALANGAN SISWA - Arsini, Ni Wayan (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
The issue of moral crisis among students has become a serious challenge for education in the digital era. This study was conducted to explore the role and pedagogical approaches of Hindu Religious Education in responding to moral decline among students. The research employed a qualitative content analysis method with a literature study approach. Data were collected from primary sources namely Hindu scriptures such as the Bhagavad Gita and Sarasamuccaya, and secondary sources in the form of textbooks and scientific articles. Data were analyzed thematically through open coding, categorization into descriptive themes, and synthesis of analytical themes. The findings show that the internalization of Hindu ethical values such as Tri Kaya Parisudha, Catur Paramita, Tri Parartha, and Tri Hita Karana has strong relevance in shaping students’ character. These values function not only as normative teachings but as pedagogical tools for developing moral reasoning, empathy, and spiritual consciousness. The study found that the moral crisis is not solely due to technological disruption or weak family support, but also due to a lack of reflective, affective, and contextual character education. Therefore, the study suggests that Hindu Religious Education should be reformulated into an integrative and transformative learning space that bridges cognition, affection, and spiritual practice. The goal is to produce students who are not only intellectually competent but also ethically responsible and spiritually grounded.